1999
DOI: 10.1038/sj.ijo.0800785
|View full text |Cite
|
Sign up to set email alerts
|

Weights of parents and infants: Is there a relationship?

Abstract: OBJECTIVE: To assess the relationship between the measures of body weights of parents and those of their children during the ®rst two years of life. SUBJECTS: Seventy-eight infants born to obese (`high risk') or nonobese (`low risk') mothers. METHODS: Weight, weight for length and skinfold thicknesses of the high and low risk infants were measured at 3 months, 12 months and 24 months of age. A multiple linear regression analysis assessed the contributions of nine risk factors, including paternal and maternal b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
31
2

Year Published

2002
2002
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 17 publications
2
31
2
Order By: Relevance
“…In most cases overweight parents create and sustain an 'obesogenic' environment (that is, high-caloric diets and physical inactivity) for themselves and their children. 14 Although other similar studies have reported a much stronger and significant risk relationship between maternal and Perinatal predictors of overweight at preschoolers G Moschonis et al childhood overweight, 14,48 such an association was not observed in the present study. This could be attributed to a higher underreporting of body weight by children's mothers than fathers and is reflected to the much higher percentage of children having an overweight father than children having an overweight mother (43.2 vs 8.1%), thus representing a limitation of the present study.…”
Section: Discussioncontrasting
confidence: 76%
“…In most cases overweight parents create and sustain an 'obesogenic' environment (that is, high-caloric diets and physical inactivity) for themselves and their children. 14 Although other similar studies have reported a much stronger and significant risk relationship between maternal and Perinatal predictors of overweight at preschoolers G Moschonis et al childhood overweight, 14,48 such an association was not observed in the present study. This could be attributed to a higher underreporting of body weight by children's mothers than fathers and is reflected to the much higher percentage of children having an overweight father than children having an overweight mother (43.2 vs 8.1%), thus representing a limitation of the present study.…”
Section: Discussioncontrasting
confidence: 76%
“…Stunkard et al 38 suggested that this risk relationship does not emerge until at least 3 to 4 years of age, but the results here show that children who were born to obese mothers were twice as likely to be obese by 2 years of age.…”
Section: Discussioncontrasting
confidence: 44%
“…Importantly, evidence for a genetic contribution to adiposity, for which there is strong evidence in later life, 21 is very weak for the first 2 years of life. 22 Body weight in this period bears little relationship to the presence of parental obesity, with low values of heritability until the age of 3. 22 In addition obesity (defined as BMI Ͼ85th centile) in the first 2 years is not a significant predictor of obesity in early adulthood.…”
Section: Discussionmentioning
confidence: 99%
“…22 Body weight in this period bears little relationship to the presence of parental obesity, with low values of heritability until the age of 3. 22 In addition obesity (defined as BMI Ͼ85th centile) in the first 2 years is not a significant predictor of obesity in early adulthood. 7 These studies suggest that the gain in weight-for-length that we have observed between 1 and 6 months of age is less likely to be mediated by genetic factors and may not be important in the long-term prediction of obesity.…”
Section: Discussionmentioning
confidence: 99%